An improved method for high‐efficiency coal mine methane drainage: Theoretical analysis and field verification. Issue 6 (9th October 2018) - Liu, Qingquan; Zhou, Hongxing; Cheng, Yuanping; Shu, Longyong; Ullah, Barkat
Abstract: Degassing a coal seam with in‐seam boreholes is an important method for mitigating the gas hazards in the underground coal mine. However, the low strength of the outburst‐proven coal limits the borehole sealing performance and borehole space maintaining, and thus influences the drainage performance of in‐seam boreholes. This study was conducted to seek a method to improve the sealing performance and borehole space maintaining for high‐efficiency CMM drainage. A visco‐elastic plastic model involving the plastic softening and dilatancy features for soft coal was proposed, and the deformation, shrinkage, and fracture characteristics of the coal surrounded a borehole and a roadway were analyzed. An enormous amount of connective fractures generated in the failure zone and the plastic zone, and the plastic zone develops timely for the creep behavior of coal, which aggravates the difficulties of borehole sealing. A comprehensive approach including the theoretical method and the technical method was developed to determine the proper sealing depth which can significantly influence the sealing performance. The sieve tubes made of high‐density polyethylene has been used to maintain the borehole space during the scheduled pre‐drainage period. A series of field tests were conducted in an outburst‐proven coal seam to verify the feasibility of the comprehensive approach and the borehole space maintaining method. Field tests showed that the comprehensive approach to determine the proper sealing depth and the installing of sieve tubes to protect the borehole space can provide favorable conditions for maximum CMM pre‐drainage from outburst‐prone coal and maximum utilization of the in‐seam boreholes. Abstract : Degassing coal seam with boreholes is an important method for mitigating the gas hazards in the underground coal mine. Two improvements, including presetting sieve tubes and proper sealing depth, are proposed to enhance the methane quality and quantity in pre‐drainage.